Clinical signs of bruxism in CrossFit® practitioners: observational study - Igor Ferreira Batista RIBEIRO; Karina Miranda LIEUTHIER; Gabriela De Sena FERREIRA; Vanara Florêncio PASSOS; Raniel Fernandes PEIXOTO; Sandra Maria Abreu NOGUEIRA; Paula Jordani ONGARO; Lívia Maria Sales Pinto FIAMENGUI (Dental Press Editora, 2024)
ABSTRACT Introduction: CrossFit® is a physical training method that aims to promote physical fitness through the development of components such as aerobic capacity, strength and muscular endurance. Data regarding bruxism behaviors in CrossFit® practitioners are scarce, but previous studies have shown increased dental clenching behavior during weightlifting practices. Objective: The present study aimed to evaluate clinical signs of bruxism in CrossFit® practitioners. Methods: The sample comprised a convenience sample of CrossFit® practitioners (n=57), of both genders, aged 19-58 years. Outcome variables were as follows: Oral Behavior Checklist, the International Physical Activity Questionnaire and the Standardized Tool for the Assessment of Bruxism. Data were expressed in terms of absolute values and percentages. Spearman's correlation and Fisher exact tests were used for statistical analysis, and a significance level of 5% was considered. Results: The mean age was 32.82 years, with a female majority (63.15%). CrossFit® practitioners frequently reported clenching their teeth during training practice (61.40%) and presented linea alba (82.45%), lip impression (54.38%), tongue impression (26.31%), bone exostosis (19.29%), tooth wear (61.40%) and non-carious cervical lesions (35.09%). Conclusions: No correlation was found between clinical signs of bruxism, oral behaviors and physical activity intensity; however, the results suggest that individuals who practice CrossFit® training have oral behaviors that can cause morpho-functional changes in the stomatognathic system, especially the habit of clenching their teeth during training. In addition, data emphasize the need for dental health education among CrossFit® practitioners, and more studies with a representative sample are necessary.